Answer:
(- 8, 14) and (- 1, 4)
Explanation:
given the 2 equations
9x + 2y = - 44 → (1)
2x + 6y = 68 → (2)
To eliminate the y-term multiply (1) by - 6 and (2) by 2
- 54x - 12y = 264 → (3)
4x + 12y = 136 → (4)
Add (3) and (4) term by term
(- 54x + 4x) + (- 12y + 12y) = (264 + 136)
- 50x = 400 ( divide both sides by - 50 )
x = - 8
Substitute x = - 8 into either (1) or (2) for y
(1) → - 72 + 2y = - 44 ( add 72 to both sides )
2y = 28 ( divide both sides by 2 )
y = 14
solution is (- 8, 14)
given the 2 equations
4x + 2y = 4 → (1)
3x - y = - 7 → (2)
to eliminate the y-term multiply (2) by 2
6x - 2y = - 14 → (3)
Add (1) and (3) term by term
(4x + 6x) + (2y - 2y) = (4 - 14)
10x = - 10 ( divide both sides by 10 )
x = - 1
substitute x = - 1 in either (1) or (2) for y
(1) → - 4 + 2y = 4 (add 4 to both sides )
2y = 8 ( divide both sides by 2 )
y = 4
solution is (- 1, 4)